2014
DOI: 10.1016/j.sapharm.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The association of subjective workload dimensions on quality of care and pharmacist quality of work life

Abstract: Background Workload has been described both objectively (e.g., number of prescriptions dispensed per pharmacist) as well as subjectively (e.g., pharmacist’s perception of busyness). These approaches might be missing important characteristics of pharmacist workload that have not been previously identified and measured. Objectives To measure the association of community pharmacists’ workload perceptions at three levels (organization, job, and task) with job satisfaction, burnout, and perceived performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 46 publications
1
57
0
8
Order By: Relevance
“…In addition, objective measurements such as attendance and hospitalization of patients in hospital wards provide useful information about healthcare staff's workload dimensions including physical, emotional, and cognitive ones (22). From the human factor point of view, excessive workload in healthcare shows its effect in two forms: First, patient-related outcomes and providing care including patient safety events and quality of healthcare; and second, healthcare staff-related outcomes such as quality of work, satisfaction, and job burnout (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, objective measurements such as attendance and hospitalization of patients in hospital wards provide useful information about healthcare staff's workload dimensions including physical, emotional, and cognitive ones (22). From the human factor point of view, excessive workload in healthcare shows its effect in two forms: First, patient-related outcomes and providing care including patient safety events and quality of healthcare; and second, healthcare staff-related outcomes such as quality of work, satisfaction, and job burnout (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of work life is comprehensive and increasing employee satisfaction and education helps them adapt to change [8]. Studies have found that the effect of different aspects of the quality of work that influence the quality of patient care include life organizational variables such as organizational conditions [9], occupational stress [10], organizational support from the medical staff [11], workload [12], job satisfaction [7,13], and occupational burnout [9,14,15]. Quality of work life can affect staff performance [16] and job engagement [17] and the factors also predict the quality of organizational service.…”
Section: Introductionmentioning
confidence: 99%
“…Já o estudo realizado por Chui et al 20 , em Wisconsin, associa a síndrome em questão à insatisfação no trabalho em farmácias comunitárias.…”
Section: Resultsunclassified
“…Dentre os doze artigos encontrados utilizando os descritores e as bases de dados, sete abordavam fatores estressores relativos à profissão 13,21,22,24,27-29 e cinco abordavam especificamente transtornos de ordem mental 20,23,25,26,30 . Dentre os sete artigos que abordam fatores de estresse relacionados aos profissionais de farmácias, o de Lea et al 22 e o de Hassell et al 24 são revisões bibliográficas que compartilham diversos artigos em suas referências, apresentando, consequentemente, fatores estressores similares, causando a falsa impressão de estressores semelhantes em trabalhos distintos.…”
Section: Discussionunclassified
See 1 more Smart Citation